Antiviral potential of proton-type zeolite - Yuka Kimura; Masanori Takemoto; Noriko Nakamura; Takeshi Ichinohe; Makoto Nakakido; Kenta Iyoki; Seiichi Ohta; Nobuhiro Miyamae; Yuki Egami; Koichi Sato; Tatsuya Okubo; Kouhei Tsumoto; et al. (PLoS ONE, 2025)
This study reports the potent antiviral ability of proton-type zeolites without the aid of any metal cations. Antiviral activities of zeolites with different topologies and chemical compositions are investigated using M13 phage and influenza virus. Proton-type zeolites exhibit excellent antiviral activity, equivalent to 99% inactivated. Antiviral tests using a centricon device suggest that direct contact of viruses on the external surface of zeolites is required to inactivate the viruses. This discovery is of importance in an interdisciplinary research field covering both zeolite science and virological science and shed light on the possibility of the development of low-cost and environmentally friendly antiviral zeolites.